Enhancing Early Childhood Social-Emotional Skills through Innovative Interactive Learning Media - Hikmah Hikmah; Sri Kuswantono Wongsonadi; Sofia Hartati; Yudrik Jahja (Asian Journal of Social and Humanities, 2024)
This study evaluates the impact of innovative interactive learning media on social-emotional skill development in preschool-aged children. Using a mixed-methods approach, the research compared social-emotional growth between an experimental group that engaged with interactive media and a control group that used traditional storybooks. Six key social-emotional skills were assessed: empathy, emotional regulation, cooperation, communication, conflict resolution, and self-awareness. Results indicated significant improvements in the experimental group across all skill parameters, with the greatest gains in communication and conflict resolution. Independent t-tests revealed that the experimental group’s progress was significantly greater than that of the control group, with large Cohen’s d effect sizes underscoring the practical relevance of these outcomes. Qualitative feedback from educators and parents further supported these findings, emphasizing how interactive media fostered active engagement and offered opportunities for children to practice social skills in real-time scenarios. This study highlights the effectiveness of interactive media as a tool for early childhood social-emotional learning and recommends further exploration of its potential across varied educational settings.